2003
DOI: 10.1021/es0343050
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Sorption and Desorption on Zeolitized Tuffs from the Nevada Test Site

Abstract: Because of the hundreds of nuclear weapon tests conducted on the Nevada Test Site (NTS) during the Cold War, the migration of radionuclides and contaminants is a potential concern. The mobility of these compounds and our ability to remediate contaminated sites are controlled by sorption and desorption processes, which depend frequently on the nature of the contaminant, the mineralogy of the site, and the geochemical conditions. The sorption and desorption behavior of strontium (Sr) and lead (Pb), two metal cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The values are much below those corresponding to inner sphere complex formation (chemical complexation). This is in line with the [11].…”
Section: -Sorption Isotherm Modelssupporting
confidence: 90%
See 3 more Smart Citations
“…The values are much below those corresponding to inner sphere complex formation (chemical complexation). This is in line with the [11].…”
Section: -Sorption Isotherm Modelssupporting
confidence: 90%
“…The sorption uptake of Sr was observed to increase with decreasing ionic strength of background solution and desorption of this ion from a sample of zeolitic tuffs, containing clinoptilolite, was reported to be enhanced by increased background electrolyte concentration [11]. The same study reported that the fixation of Sr 2+ by clinoptilolite occurs via ion-exchange in addition to outer sphere complex formation, with the latter being pH dependent.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Um and Papelis [160] studied column experiments to investigate the effect of natural colloids on the transport of a strongly sorbing metal, lead (Pb 2+ ) under different geochemical conditions. Here, natural colloids were generated from zeolitized tuffs from the Nevada Test site (NTS).…”
Section: Laboratory Studies On Colloid-facilitated Transport Of Othermentioning
confidence: 99%